Building Civic Capacity Using a Holistic Approach to Public Library Service: a Participant Researcher’s Perspective on Social Justice in the Cayman Islands Public Library Service - Williams-Cockfield, Kaurri C. (Qualitative and Quantitative Methods in Libraries, 2017)
This paper discusses the implications and potential impact of the public library service on the social, political and economic conditions in the Cayman Islands. The Cayman Islands is currently facing a variety of quality of life issues including unemployment, declining industries and a dynamic government landscape. Underpinning these issues is the need for Caymanians to participate, from an informed perspective, in the decisions directly impacting quality of life. To this end, Caymanians will need to be information literate, civically engaged and aware of the global market and, cognizant of and participatory in the preservation of their individual cultural heritage in order to ensure on-going economic viability for the country. An analysis of the information access practices in the Cayman Islands show how the restructuring of the public library service along four strategic directions supports an expanded the civic capacity for Caymanians.